A Novel Requirements Analysis Approach in SPL based on Collateral, KAOS and Feature Model - Khan, Fazal Qudus; Musa, Shahrulniza; Tsaramirsis, Georgios; Khan, Sohail (International Journal of Engineering and Technology, 2018)
Software product lines (SPL) can speed up the production of software through the auto-generation of products and related subproducts, reducing the need for developer involvement. There are some proposals for defining the requirements for SPL, but they do not propose any method for identifying the eco-systems required for a successful life cycle of the generated product. In this research we propose the use of MEASUR Collateral Analysis for the purpose of identification of all the environmental systems and KAOS goal modeling linked with a feature model for ensuring that the features are aligned with the goals and objectives of the focal system. The proposed approach is demonstrated with a case study.